A preliminary study on conversion efficiency improvement of a multi-junction PV cell with MPPT - Das, Narottam; Wongsodihardjo, H.; Islam, Syed (2016)
© Springer International Publishing Switzerland 2016. This chapter presents a preliminary study conducted to improve photovoltaic (PV) cell conversion efficiency using MATLAB/Simulink platform. The study uses multi-junction solar cell and investigates the maximum performance compared with a conventional silicon PV cell. Maximum Power Point Tracker (MPPT) is applied to assess the conversion efficiency of the PV system. Study integrates thermoelectric generator (TEG) with PV modules because the PV cells work by converting high frequency irradiation where as a TEG has the ability to convert wasted low frequency heat to the electricity. The combination delivers more power and contributes to enhance the conversion efficiency of a PV system. The simulation results show that a tandem cell can provide a considerable higher power with a conventional PV cell operation.